Breast data from preoperative and surgical cases - Bodén, Anna (AIDA Data Hub, 2023)
Whole slide imaging of 102 primary diagnosed breast cancers. In this dataset one representative image from the preoperative biopsy have been manually selected and matched with one image representative from the surgically removed invasive tumour. Both biopsy and whole section are presented as one case and contain 2 HE stained slides per case. The section from the surgical resection is from one piece as default, biopsies may vary from 1-3 per slide. Breast cancer cases were consecutively selected from the laboratory information system based on diagnosis including only Invasive breast cancer (NST) and Invasive lobular carcinoma (ILC). Each slide has been evaluated in clinic by at least one senior consultant in breast pathology and controlled before extraction to this dataset by an additional independent senior breast pathologist. No neoadjuvant cases included. No male breast cancers included. The cases are anonymised and exported from the digital archive at the Department of Clinical Pathology in Linköping, Region Östergötland.
Keywords: Breast cancer; Pathology; Whole slide imaging; Medical and Health Sciences; Medicin och hälsovetenskap